Curcuma Longa (turmeric): from traditional applications to modern plant medicine research hotspots - Wei-Wei Tian; Li Liu; Ping Chen; Dong-Mei Yu; Qing-Miao Li; Hua Hua; Jun-Ning Zhao (Chinese Medicine)
Abstract Turmeric, derived from the dried rhizome of Curcuma longa L., receives widespread attention because of its applications in pharmaceutical, food, cosmetic and other industries. Traditionally, it has been widely used in Ayurveda medicine and traditional Asian medicine such as traditional Chinese medicine, for treatment of digestive, respiratory and circulatory diseases, as well as skin diseases. However, a comprehensive review of traditional applications, modern clinical applications, and related products remains largely unexplored. Here, we conduct a systematic summary of its pharmacological activities, including anti-inflammatory activity, anti-oxidant activity, anti-diabetic activity, anti-tumor activity, neuroprotective activity, hepatoprotective activity, anti-microbial activity and others. Additionally, we explore the randomized controlled trials, guiding future preventive healthcare strategies and clinical practices. Furthermore, we also discuss the turmeric-related products, involving medicines, health foods, herbal dietary supplements, and cosmetics, offering novel insights into relevant product development. Totally, this review provides a comprehensive understanding of turmeric on botany, history and traditional applications, pharmacological activities, clinical applications, and related products. Finally, based on the generalized science of Chinese material madica and advanced front technologies, the future research opportunities of turmeric are briefly explored.